Parenquimal suture complications of bleading splenie lesion - Vázquez Díaz, Daniel; Pérez Penco, Ernesto; de Freitas, Lourdes; Girardi, Gino; Mariano, Raúl; Fazzio, Susana; Laso, José L; Bonaba, Roberto (Cirugía del Uruguay, 1983)
Facing locoregional infection as the main complication of paranqulmal suture of bleeding splenic lesion, comtamination as etiological factor is presented and ischemia, suture material acting as foreign body, crushing and elcctrocoagulation are studied as allowing mechanisms. An study in 25 dogs, grouped in 5 series, through bacteriological and patological examinations, is performed·. The authors conclude that parenquimal ischemia is the factor that, in major percentile, predispose to esplenic infection, been the responsible germen the staphilococus aureus in ali cases.